Lipidated cyclopropenes via a stable 3-N spirocyclopropene scaffold. Issue 37 (12th September 2018) - Kumar, Pratik; Jiang, Ting; Zainul, Omar; Preston, Alyssa N.; Li, Sining; Farr, Joshua D.; Suri, Pavit; Laughlin, Scott T.
Graphical abstract: Highlights: Cyclopropenes are popular bioorthogonal tags for ligation with 1, 2, 4, 5-tetrazines. Modification at cyclopropene alkene carbons is synthetically challenging. Synthesis of biologically relevant cyclopropene-modified lipids is described. Abstract: Lipidated cyclopropenes serve as useful bioorthogonal reagents for imaging cell membranes due to the cyclopropene's small size and ability to ligate with pro-fluorescent tetrazines. Previously, the lipidation of cyclopropenes required modification at the C3 position because methods to append lipids at C1/C2 were not available. Herein, we describe C1/C2 lipidation with the biologically active lipid ceramide and a common phospholipid using a cyclopropene scaffold whose reactivity with 1, 2, 4, 5-tetrazines has been caged.